Osteonecrosis of the femoral head in a recreational diver: Case report. (2nd January 2016) - Inklebarger, James; Taylor, Matt; Griffin, Murray
Abstract : Objectives : Osteonecrosis of the hip joint (ONHJ) is a known sequella of dysbaric events in professional divers. Its occurrence in sport divers has been rarely reported in the literature. Such a circumstance may represent a diagnostic challenge to clinicians as a potential dysbaric event may be long forgotten, and ONHJ is not typically associated with sports divers. Methods : This case study identifies the occurrence of osteonecrosis of the hip in a recreational diver, which may be related to a dysbaric event several years prior to the onset of hip joint pain and loss of function. Discussion : Advances in recreational diving gear (technical diving) have allowed for greater depths and dive duration. However, these technological developments may have outpaced awareness of the significantly increased risks of permanent illness. A review of the literature also indicates that there may be inaccuracies in some decompression tables which could unknowingly predispose dysbaric events. As ONHJ carries a high rate of morbidity and may have a variable and delayed presentation, it is recommended that clinicians recognize this differential in recreational divers presenting with joint pain.